Effect of olive pomace extract application and packaging material on the preservation of fresh-cut royal gala apples - Madureira, Joana (2020)
The efficiency of natural olive pomace extracts for enhancing the quality of fresh-cut apples was compared with commercial ascorbic acid and two different packaging films (biodegradable polylactic acid (PLA) and oriented polypropylene (OPP)) were tested. The composition of atmosphere inside the packages, the physicochemical parameters (firmness, weight loss and color), the microbial load, total phenolic content and antioxidant activity of fresh-cut apples were evaluated throughout 12 days of storage at 4 degrees C. After 12 days of refrigerated storage, a significant decrease in O-2 was promoted in PLA films, and the weight loss of the whole packaging was higher in PLA films (5.4%) than in OPP films (0.2%). Natural olive pomace extracts reduced the load of mesophilic bacteria (3.4 +/- 0.1 log CFU/g and 2.4 +/- 0.1 log CFU/g for OPP and PLA films, respectively) and filamentous fungi (3.3 +/- 0.1 log CFU/g and 2.44 +/- 0.05 log CFU/g for OPP and PLA films, respectively) growth in fresh-cut apples after five days of storage at 4 degrees C, and no detection of coliforms was verified throughout the 12 days of storage. In general, the olive pomace extract preserved or improved the total phenolic index and antioxidant potential of the fruit, without significant changes in their firmness. Moreover, this extract seemed to be more effective when combined with the biodegradable PLA film packaging. This work can contribute to the availability of effective natural food additives, the sustainability of the olive oil industries and the reduction of environmental impact. It can also be useful in meeting the food industries requirements to develop new functional food products.